Application of the hodrick-prescott model for the price forecast of electricity in Colombia [Aplicación del modelo de hodrick-prescott para el pronóstico del precio de la electricidad en Colombia] (2019)
The Colombian electricity market aims to offer a continuous and reliable service. However, the specific characteristics associated with its high dependence on hydroelectric generation, the technical limitations that allow its storage and the passive behavior of demand jeopardize the fulfillment of this objective. Uncertainty about future results has a significant impact on investment prospects, which consequently restricts the diversification of the energy matrix. In this context, among the mechanisms considered for the valuation of new projects and regulatory reforms, the interest to study the short and long-term behavior of the price of electricity stands out. The tool proposed in this paper develops an algorithm based on the Hodrick and Prescott filter for the Colombian market, which allows identifying the behavior of the cycle and the price trend, contributing to the decision making in the sector. © 2019, Associacao Iberica de Sistemas e Tecnologias de Informacao. All rights reserved.